Prevalence of bacterial types in Wagner grade three of diabetic foot ulcer - Mahmoud, Halah; Abid Ali, Sameer; Jaddue, Dhia (Iraqi Journal of Science, 2023)
Diabetic foot ulcer (DFU) is one of the chronic wound infection and leads to non-traumatic lower limb amputation. Advances in diabetes research are significant and much needed because diabetes is on the rise worldwide and is considered by some experts already to be at an epidemic level. Among diabetic patients 70% were males and 30% were females. Aerobic bacteria 104(82%) were the most frequently isolated than anaerobic bacteria 23(18%). Among aerobes Gram negative bacteria 67(64.4%) were more commonly isolated than Gram positive 37(35.5%). The three most frequently found that S. aureus 28(22%) followed by P. mirabilis 22(17.3%) then E. coli 14(11%). Among anaerobic bacteria Gram negative bacteria 16(69.5%) were predominantly isolated than Gram positive bacteria 7(30.4%). The most probably isolated Veilonella spp. 10(7.9%) followed by Peptostreptococcus anaerobius 6(4.7%).